Near quantitative synthesis of urea macrocycles enabled by bulky N-substituent - Yingfeng Yang (Nature Portfolio, 2021)
Macrocycles are molecular structures extensively used in the design of catalysts, therapeutics and supramolecular assemblies but synthesis procedures that can produce macrocycles in high yield under high reaction concentrations are rare. Here the authors report the use of dynamic hindered urea bond for the construction of urea macrocycles with high efficiency.